A nightmare on Elm Street 5. The dream child [videorecording (DVD)] - Craven, Wes; Hopkins, Stephen, 1959-; Shaye, Robert; Harvey, Rupert; Englund, Robert, 1947-; Wilcox, Lisa, 1964- (Nightmare on Elm Street collection., 1999)
Unable to overpower Alice, the Dream Master who vanquished him, Freddy haunts the dreams of Alice's unborn child and preys upon her friends with sheer horror.